Oh, buoy! - Lantz, Francess Lin, 1952- (New York : HarperEntertainment, 2003)
Isobel wonders whether she has won a surf company sponsorship on her own merit or through the influence of her new boyfriend.
Keywords: Surfing -- Fiction; California -- Fiction; Young adult fiction; Love stories; Sports stories